Conformal Modulus of the Exterior of Two Rectilinear Slits - D. Dautova; S. Nasyrov; M. Vuorinen (SPRINGER HEIDELBERG, 2022)
We study moduli of planar ring domains whose complements are linear segments and establish formulas for their moduli in terms of the Weierstrass elliptic functions. Numerical tests are carried out to illustrate our results.